A content analysis of appeals in food advertisements for children on online TV streaming - Fong, Belinda Fong Chong *; Izzal, A. Z. (School of Media and Communication, Taylor's University Malaysia, 2019)
The increasing number of obese children has doubled over the past two decades and represents a major public health problem everywhere in the world. This problem is escalated with easy Internet access, where online TV programming with unrestrained food advertisements are easily available to children. Recognising the increasing purchasing power of children, food marketers are now focusing on this cohort as a profitable target group. While previous studies have examined food advertisements that target children and how these affect their food choices, this study goes one step further by identifying major forms of persuasive appeals utilised by the food marketers in such advertisements. Using content analysis to study advertisements targeting children on Internet TV streaming via children’ channels, this study identified 21 emotional appeals and 15 rational appeals employed by food marketers in their advertisements. The findings of this study show that children are more susceptible to the emotional contents of the advertisements, (where it appeals to the children’s emotional desires) rather than the rational quality of the advertisements (where the logic of health and nutrition claims are not salient concerns).